Microzonation Study Based on Ground Amplification for Erzincan City - Mehmet Özyazıcıoğlu; Kemal Dönmezçelik; Süleyman N. Orhan; M. Yener Özkan (Doğal Afetler ve Çevre Dergisi)
Nearly all regions in Erzincan lie on a first degree earthquake zone. In the plains of the city, the thickness of the alluvial layer over the bedrock is about 1 km. In this regard, it is clear that a detailed ground amplification analysis is required for the city settlement area. In this research, soil amplification analyses based on equivalent linear one dimensional shear wave theory have been made for the province of Erzincan. For this purpose, borehole (max depth 275 m) data pertaining to DSI (State Water Works) drilled between 1960 and 1980 for ground water exploration are used. The equivalent linear ground motion analyses have been accomplished by EduShake/ProShake, a one dimensional shear wave analysis program. Eight different scaled real ground motion acceleration time histories are used to obtain surface motion PSA (Pseudo Spectral Acceleration). The average of PSA at each boring location is plotted together with bed rock outcrop PSA and 2007-Turkish Earthquake Code Design Spectrum. The amplification ratios for each period are computed by dividing surface PSA to bedrock outcrop PSA. The map of the city is divided into microzones, representing each boring log to display periods where computed amplifications are observed.